CONVERSANT WIRELESS LICENSING S.A.R.L. v HUAWEI TECHNOLOGIES CO LTD (NO. 2). Issue 9 (15th December 2018) - ,
Abstract: H1 Patents – European patents – Telecommunications – Standards essential patents – Infringement – Claim for determination of a global FRAND licence – Jurisdictional challenges – Justiciability – Forum conveniens – Permission to appeal – Stay of the proceedings pending appeal – Proper construction of CPR r. 11 – Whether taking steps in the action pending appeal would amount to submission to the jurisdiction – Practice – Wording of orders for directions pending appeals on jurisdiction